Effect of Low-Energy and Low-Protein Diets on Production Performance of Boiler Breeders and Hatching Parameter - Nideou , D.; N`nanle, O.; Teteh, A.; Decuypere, E.; Gbeassor, M.; Tona, K. (International Journal of Poultry Science, 2017)
Background and Objective: A major challenge in broiler breeder management is the nutritional requirement and the effect of feed formulation on breeder performance. Metabolizable energy and crude protein levels are two important nutritional parameters for evaluating poultry feed. The purpose of this study was to evaluate the effect of low-protein and low-energy diets on the performance of Sasso breeders. Materials and Methods: The experiment was performed with 120 Sasso breeders divided into 3 groups (control group, low-protein group and low-energy group) of 40 birds each. Feed intake, body weight, egg weight and egg component weights were recorded weekly. At 35 weeks of age, a total of 600 settable eggs were collected in 7 days and stored at 15°C before incubation. Prior to setting for incubation, eggs were numbered, weighed and assigned to 4 replications of 50 eggs each diet/treatment. Results: Results indicate that breeders of the control diet group exhibited increased body weight (p<0.05) with heavier eggs (p<0.05) and an increased ratio of albumen weight to egg weight (p<0.01) as compared with the groups with the low-energy diet and the low-protein diet (p<0.05). In addition, day-old chicks from eggs of the control group were heavier (p<0.05) than those from eggs of both the low-energy and low-protein diet groups. Conclusion: Low-protein and low-energy diets during the laying period negatively affect the feed intake and feed conversion ratio. These diets also affect the egg weight and ratios of albumen, yolk, shell and chick weight. No significant differences were observed regarding hatchability and blood serum concentration levels of total protein, triglycerides and glucose.